WOOD PULP FOR POLYMER COMPOSITES PRODUCTION - Agnes, Erick Afonso; de Mello, Tânia Vieira; Hillig, Éverton; Miyahara, Ricardo Yoshimitsu (Floresta, 2020)
The use of cellulosic fibers in composites is advantageous compared to inorganic materials, because they present lower density, abrasiveness and cost, besides the renewable origin. This study aimed to evaluate the influence of wood pulp obtained by the chemical (bleached and unbleached) and mechanical process, and wood-flour of Pinus taeda as reinforcement in low density polyethylene (LDPE) matrix. The composites were extruded and the specimens molded by compression. The samples were characterized by thermal analysis, density, mechanical properties and scanning electron microscopy (SEM). The incorporation of the wood pulps and the wood flour in the matrix improved the composites mechanical properties and reduced the rate of material degradation. All fibers types acted as nucleating agents because the composites had better mechanical properties than pure LDPE. There was influence of the studied parameters on tensile and flexural strength and the interactions were significant. In general, the highest values of strength and stiffness were obtained with the use of thermo-mechanical process pulp as reinforcement and the lowest values with the use of unbleached chemical process pulp. micrographs analysis showed that the coupling agent was effective for compatibilizing the wood fibers with the LDPE in the composites. It was possible to produce composite materials with good physical and mechanical properties and improved thermal stability by experimental model.